Penyuluhan Pencegahan Penyakit Demam Tifoid Pada Siswa-Siswi Di SMAS Santa Lusia Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Christine Sibuea (LPPM Universitas HKBP Nommensen, 2021)
Typhoid fever is an infectious disease caused by Salmonella tyhphii bacteria. Typhoid fever is transmitted through the faecal orally when food or drink is contaminated with Salmonella tyhphii bacteria due to lack of hygiene of food or drinks. Clean and Healthy Living Behavior (PHBS) is very important to prevent the transmission of typhoid fever. This counseling aims to provide education about typhoid fever, including how to prevent the transmission of typhoid fever. This counseling was given to students of class XI Santa Lusia Senior High School, Percut Sei Tuan District. Outreach is provided through presentation, question and answer and online feedback. Feedback shows that participants can receive the information given well.